Economic consequences on early marriage: Correlation with women’s employment and education mobility - Purmini, Purmini; Nopiah, Ririn; Hutapia, Hutapia; Ramah, Nabila Miftaahur (Journal of Economics and Business Letters, 2025)
This study investigates the socioeconomic consequences of early marriage in Bengkulu Province, Indonesia, focusing on women's mobility in terms of education and employment. Drawing on 11,553 microdata observations from the 2024 SUSENAS, the analysis establishes that early marriage is systematically correlated with profound intergenerational disadvantages. The findings indicate that early marriage is associated with lower educational attainment, with only 18 percent experiencing upward educational mobility compared to their parents. In the labor market, women’s labor participation tends to be linked to parental employment, as mothers’ and fathers’ work status is correlated with a 51.6 percent and 33.6 percent higher probability of employment, respectively. Conversely, low parental education and large household sizes were identified as key determinants of economic vulnerability. In conclusion, early marriage is closely linked to intergenerational socioeconomic disadvantages, such as limited educational and employment opportunities. Therefore, policy interventions must strategically focus on expanding educational access and enhancing quality employment opportunities in rural settings to facilitate inclusive human capital development.